x- 9/4 = - 3/8

3 answers

To solve for x, we need to isolate it on one side of the equation.

Given: x - 9/4 = -3/8

We can start by adding 9/4 to both sides of the equation to eliminate the negative fraction on the left side:

x - 9/4 + 9/4 = -3/8 + 9/4

Simplifying the right side:

x = (9/4) + (9/4)

Now, add the fractions:

x = (9 + 9) / 4

x = 18/4

Simplify the fraction:

x = 9/2 or x = 4.5

Therefore, the solution to the equation is x = 4.5.
wrong
Apologies for the previous incorrect response.

To solve for x in the equation x - 9/4 = -3/8, we can start by adding 9/4 to both sides of the equation to isolate x:

x - 9/4 + 9/4 = -3/8 + 9/4

Simplifying the left side:

x = -3/8 + 9/4

To add these fractions, we need a common denominator. The least common multiple of 8 and 4 is 8. So we can rewrite the fractions with the common denominator of 8:

x = -3/8 + (9/4) * (2/2)

x = -3/8 + 18/8

x = ( -3 + 18 ) / 8

x = 15/8

Therefore, the solution to the equation is x = 15/8.